Correlation between localized plastic deformation and localized corrosion in AA2099 aluminum‐lithium alloy. (7th September 2015) - Huang, Weijiu; Ma, Yanlong; Zhou, Xiaorong; Meng, Xiaomin; Liao, Yi; Chai, Linjiang; Yi, Yanan; Zhang, Xinxin
Abstract : Localized corrosion in an AA2099‐T83 aluminum–lithium alloy has been correlated with localized plastic deformation (LPD) introduced by cold working. The high population density of dislocations in the slip bands associated with LPD promoted preferential precipitation of needle‐shaped T1 (Al2 CuLi) phase during artificial aging. Consequently, preferential attack of the electrochemically active T1 phase in corrosive environment resulted in selective corrosion of the bands, leading to the development of the characteristic morphology of narrow, parallel volume of corrosion. Copyright © 2015 John Wiley & Sons, Ltd.